Intestinal Microbial-Derived Sphingolipids Are Associated with Childhood Food Allergy - Lee-Sarwar, Kathleen; Kelly, Rachel S.; Lasky-Su, Jessica; Moody, D. Branch; Mola, Alex R.; Cheng, Tan-Yun; Comstock, Laurie E.; Zeiger, Robert S.; O'Connor, George T.; Sandel, Megan; Bacharier, Leonard B.; Beigelman, Avraham; et al. (Journal of allergy and clinical immunology, 2018)
Methods Metabolomic and bacterial microbial composition profiling was performed on infant fecal samples from 14 subjects who developed food sensitization and clinical food allergy by age 3 years, 32 with food sensitization but no clinical food allergy, and 37 controls. Results Sphingolipid biosynthetic metabolites had higher relative abundances in subjects with food sensitization vs allergy (adjusted logistic regression p=0.01) and controls (p=0.02), and were associated with Bacteroides spp. iNKT cell activity of fecal lipid fractions was positively associated with relative abundances of several sphingolipid metabolites, Bacteroides fragilis (Spearman rho=0.50, p<0.001), and food sensitization vs allergy (Wilcoxon test p=0.03).